2001
DOI: 10.1590/s0034-89102001000400010
|View full text |Cite
|
Sign up to set email alerts
|

Ecologia de mosquitos em áreas do Parque Nacional da Serra da Bocaina: II -- Freqüência mensal e fatores climáticos

Abstract: Resumo ObjetivoEstabelecer a influência exercida pelos fatores climáticos na freqüência mensal da fauna de mosquitos em áreas do Parque Nacional da Serra da Bocaina, Vale do Paraíba, SP. Métodos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 12 publications
0
15
0
2
Order By: Relevance
“…fajardi was most abundant during the cooler season. This pattern is related to the fact that the eggs of this species develop more successfully when the water in the larval habitat is clean, cold and flowing (Baerg & Boreham 1974), which does not occur during the warmer months, as noted by Guimarães et al (2001).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…fajardi was most abundant during the cooler season. This pattern is related to the fact that the eggs of this species develop more successfully when the water in the larval habitat is clean, cold and flowing (Baerg & Boreham 1974), which does not occur during the warmer months, as noted by Guimarães et al (2001).…”
Section: Discussionmentioning
confidence: 95%
“…Some authors have observed that the availability of larval habitats (Hayes & Charlwood 1979, Guimarães et al 2000 and the abundance of mosquitoes are mainly controlled by rainfall (Guimarães et al 2001), even in artificially altered environments (Forattini et al 1996) like PAHS. Montes (2005) reported that among the climatic factors analysed, temperature was most highly correlated with the number of individuals caught in the study area of Serra da Cantareira (state of São Paulo).…”
Section: Discussionmentioning
confidence: 99%
“…In the tropics, water in breeding sites has to rise to a critical level in order to reach the mosquito eggs, which hatch a few days after this contact; therefore, the number of culicid mosquitoes is often directly associated with the amount of rainfall (De Kruijf 1970, Souto 1994, Rocha et al 1997, Guimarães et al 2001, Montes 2005.…”
mentioning
confidence: 99%
“…Similar studies (13) (14) have reported that rainfall primarily controls the availability of breeding sites and the abundance of mosquitoes. However, the early formation of the reservoir during Phase II resulted in the fl ooding of vast areas of forest and the presence of decaying vegetation around the reservoir, which signifi cantly favored An.…”
Section: Studies Conducted Near the Itaipu Hydroelectric Plantmentioning
confidence: 52%